BASIC ASPECTS OF MEASUREMENT OF IMPAIRMENT OF LONG-TERM ASSETS OF AN ENTITY - Maisuradze, Marina (Ecoforum Journal, 2019)
Abstract The carrying value of the enterprise assets is their historical value, which is adjusted by the amount of depreciation, that represents an estimate of value and only approximately reflects the value of the asset value in time. At the same time, investors, who are the main consumers of the financial statements, are not interested in the value of the asset value of the assets, they are interested in the economic benefits, that will bring the asset in the future. IAS 36 "Impairment of Assets" requires that the economic benefits of the asset must not be reflected excessively in the financial statements. The reliable assessment of the assets reflected in the financial statements is one of the foremost. Their real value over time can be changed for various reasons. Therefore, the enterprise needs to periodically re-evaluate the assets in its disposal and determine their recoverable value. In the article, the issues of impairment of assets are discussed based on international financial standards and, the opinions on these issues are expressed. Key words: Assets impairment , Financial Statement, Rate of discount, Recoverable value, JEL Classification: M41